2020
DOI: 10.18332/tpc/119053
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and related factors of bidi smoking in India

Abstract: INTRODUCTION Bidis are the most commonly smoked tobacco product in India. Understanding bidi smoking is important to reducing overall tobacco smoking and health-related consequences in India. We analyzed 2009-2010 and 2016-2017 Global Adult Tobacco Survey (GATS) India data to examine bidi smoking and its associated sociodemographic correlates and perceptions of dangers of smoking. METHODS GATS is a nationally representative household survey of adults aged ≥15 years, designed to measure tobacco use and tobacco … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Beedi smoking and SLT use are relatively rare in young adult females in the Indian population. 14,27 Some previous studies on a similar topic have also focused only on the male population. 19,35 Although we tried to avoid many confounding factors, some of the observations in our study might remain unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…Beedi smoking and SLT use are relatively rare in young adult females in the Indian population. 14,27 Some previous studies on a similar topic have also focused only on the male population. 19,35 Although we tried to avoid many confounding factors, some of the observations in our study might remain unexplained.…”
Section: Discussionmentioning
confidence: 99%
“…Control of the tobacco epidemic is a long-term process, which is strongly related to the residents’ education, culture, health literacy, behaviour, cognition, family income and mental health. 13 14 In recent decades, some cities in China have seen rapid growth in industrialisation and modernisation and have become areas of higher economic levels. However, there is a lag in changes related to smoking intensity pattern, social and economic group composition, the tobacco epidemic trend and other factors that are different from those in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…In the past three decades, China’s economy has developed rapidly, and the national income of some regions has reached the standard of developed regions worldwide and has entered the ranks of high-income areas. Control of the tobacco epidemic is a long-term process, which is strongly related to the residents’ education, culture, health literacy, behaviour, cognition, family income and mental health 13 14. In recent decades, some cities in China have seen rapid growth in industrialisation and modernisation and have become areas of higher economic levels.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Another recent study found that bidi use was highest among those of lower education, wealth and socioeconomic status. 11 The lenient tax treatment of indigenous tobacco products is a key issue here, with bidis historically being taxed at relatively low levels because it has been perceived as the ‘poor man’s puff’, without giving due consideration to the devastating impact of the ‘puff’ on the ‘poor man’s’ health and productivity.…”
Section: Introductionmentioning
confidence: 99%